2009
DOI: 10.1111/j.1365-2214.2009.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors relating to decreased risks of adolescent suicidal behaviour

Abstract: Adolescent suicide behaviour should be a serious problem. Measures can be taken to prevent suicide by observing the factors significantly linked to suicidal behaviour. Steps can then be taken to identify adolescents who have serious suicidal ideation so that intervention can be taken to reduce the suicidal rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
56
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 27 publications
13
56
0
4
Order By: Relevance
“…As corroborated by other studies, females were more likely to report suicidal ideation and attempt in all three cities [3,4,9,12,21,24,25]. In fact, more than 72% of youth who reported attempted suicide in Vietnam were females.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As corroborated by other studies, females were more likely to report suicidal ideation and attempt in all three cities [3,4,9,12,21,24,25]. In fact, more than 72% of youth who reported attempted suicide in Vietnam were females.…”
Section: Discussionsupporting
confidence: 89%
“…For example, studies have reported suicidal ideation prevalence ranging from 2.4% to 17.4% and suicide attempt rates ranging from 3.2% to 9% [21,[23][24][25]. The reported prevalence of suicidal ideation and attempt in the Shanghai sample of the data falls within the range of extant literature.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…According to this hospital study, the prevalence of attempted suicide (36.6%), suicidal thoughts (47.2%) and preparatory acts to kill self (18.9%) were higher than rates reported in community samples elsewhere. In a Chinese study, 17.4% of students had seriously considered attempting suicide and 8.1% had made a specific plan to attempt suicide during the 12 months preceding the survey [22]. In a Turkish study, 23% of student participants reported having thoughts of killing themselves during the past 12 months or their life [23].…”
Section: Discussionmentioning
confidence: 99%